Circulatory Trauma: A Paradigm for Understanding the Role of Endovascular Therapy in Hemorrhage Control. (December 2021) - Duchesne, Juan; Taghavi, Sharven; Khan, Mansoor; Perreira, Bruno; Cotton, Bryan; Brenner, Megan; Ferrada, Paula; Horer, Tal; Kauvar, David; Kirkpatrick, Andrew; Ordoñez, Carlos; Priouzram, Artai; et al.
Abstract : ABSTRACT: The pathophysiology of traumatic hemorrhage is a phenomenon of vascular disruption and the symptom of bleeding represents one or more vascular injuries. In the Circulatory Trauma paradigm traumatic hemorrhage is viewed as injury to the circulatory system and suggests the underlying basis for endovascular hemorrhage control techniques. The question "Where is the patient bleeding?" is replaced by "Which blood vessels are disrupted?" and stopping bleeding becomes a matter of selective vessel access and vascular flow control. Control of traumatic hemorrhage has traditionally been performed via external access to the end organ that is bleeding followed by the application of direct pressure, packing, or clamping and repair of directly affected blood vessels. In the circulatory trauma paradigm, bleeding is seen as disruption to vessels which may be accessed internally, from within the vascular system. A variety of endovascular treatments such as balloon occlusion, embolization, or stent grafting can be used to control hemorrhage throughout the body. This narrative review presents a brief overview of the current role of endovascular therapy in the management of circulatory trauma. The authors draw on their personal experience combined with the last decade of published experiences with the use of endovascular techniques in trauma and present general recommendations for their evolving use. The focus of the review is on the use of endovascular techniques as specific vascular treatments using the circulatory trauma paradigm.